Cannabinoids and Viral Infections - Carol Shoshkes Reiss (MDPI AG, 2010)
Exogenous cannabinoids or receptor antagonists may influence many cellular and systemic host responses. The anti-inflammatory activity of cannabinoids may compromise host inflammatory responses to acute viral infections, but may be beneficial in persistent infections. In neurons, where innate antiviral/pro-resolution responses include the activation of NOS-1, inhibition of Ca2+ activity by cannabinoids, increased viral replication and disease. This review examines the effect(s) of cannabinoids and their antagonists in viral infections.